Interventions to enhance coping after traumatic brain injury: A systematic review - Mueller, C; Wesenberg, S; Nestmann, F; Stubbs, B; Bebbington, P; Raymont, V (Mark Allen Group, 2018)
Background/Aims: The aim of this study was to identify effective psychosocial interventions to enhance coping in people who have experienced a traumatic brain injury, in order to inform clinical practice and articulate future research directions.